Study on surface quality of GH4169 superalloy milling with ultrasonic synergistic nanofluid minimal quantity lubrication - Xuezhi Wang; Zixiang Mei; Xingchao Wang; Ning Hou; Minghai Wang (Scientific Reports)
Abstract GH4169 superalloy is extensively utilized in aerospace applications due to their exceptional high-temperature strength and oxidation resistance properties. However, its high hardness presents significant machining challenges, including rapid tool wear and poor surface quality. This study introduces ultrasonic synergistic nanofluid minimal quantity lubrication milling (USNMQLM) technology to address these machining difficulties and enhance surface integrity. The research examines USNMQLM principles, investigating tool-workpiece separation characteristics and lubrication behavior under separated cutting conditions. By building an experimental platform, the influence of processing parameters, ultrasonic variables, and cooling methods on the surface quality of milling GH4169 superalloy was studied. The results indicate that the ultrasound assisted nanofluid micro lubrication milling method has a significant effect on improving the milling surface quality. By examining the quality of milling surfaces under different processing parameters, it was found that the optimal milling surface quality was achieved when the spindle speed was 600 rpm, the feed rate was 60 mm/min, and the milling depth was 0.1 mm. In addition, by comparing conventional milling, ultrasonic vibration-assisted milling (UVAM), and nanofluid minimal quantity lubrication (NMQL)-assisted milling, it was found that under the same milling parameters, the surface roughness of ultrasonic synergistic nanofluid minimal quantity lubrication milling was reduced by 49.8%, 42.8%, and 15.2%, respectively, and the depth of plastic deformation layer was reduced by 64.6%, 61.2%, and 38.7%, respectively. In addition, this processing method has a certain effect on improving the hardness of the processed material, with a 20.8% increase compared to the substrate hardness.